Research and Development a Web Application Management for University Students in Colombia (2017)
The popularization of the Internet and the use of ICT has brought great and innumerable advantages to multiple users that are interconnected at the time, the arrival of new wireless technologies with improved bandwidth and data transfer protocols has led to a new concept called mobile and ubiquitous networks. We are in a purely mobile world, the arrival of smartphones and tablets with power and efficient operating systems and features that not stop surprising have been adapted by many users as communication devices, entertainment, learning and a number of ends that have changed. The way, we interact in the world and manage to create a concept of mobility in the new holistic dimension of the Web. That is why the CUN and his research Axon group cannot be oblivious to these becoming and technological progress, which is why this project of applied research focuses on making an application for consultation of tutoring students different educational programs of the center seat of the CUN using a Web application that can enhance the timing of academic work by the student teacher and create better professionals and citizens in our country in all the preparatory cycle